Molecular docking of Vitamin D3 Receptor (VDR) with potential herbal substance as ligand to prevent excessive hair loss in menopausal women - Parawangsa, Aditya; Sugito, Syailendra Karuna; Ayu Ananda Latifa, Ariestiana; Dinda Safira, Nadya; Ayuthaya, Shafa; Rahmalia Az Zahra, Raissa (UI Scholars Hub, 2022)
Hair loss is commonly found in menopausal women. Hair loss is one of the consequences of hormonal dynamics when a woman stops having menstrual cycle, which affect calcium and vitamin D level in the body. Although it is clear enough that hormonal adjustment is required, older people and another sociodemographic factor prefer herbal-based therapeutic rather than synthetic-based due to tradition and positive experience factors. This study is an in-silico study which aims to point out the possible ligand candidates that can work as Vitamin D Receptor (VDR) agonists. We perform molecular docking using Autodock version 4.2 with the criteria of Lamarckian GA. VDR (PDB ID: 1TXI) was docked with ten compounds and one native ligand, then analyzed using Autodock 4.2. Dolichosterone, Gartanin, and (-)-Matairesinol, Luteolin, 5-HETE, Sinapyl glucoside, and geraniol, in order shows smallest to bigger binding energy when simulated in the software (-9.72, -7.70, -7.20, -6.88, -5.76, -5.71 kcal/mol). Thus, we found that these compounds are potential to become VDR agonist. Further research is still required to determine each compound drug potential and maximize therapeutic concentration for medicinal purposes.